Efektifitas Penerapan Penggalangan Dana Dalam Aplikasi Pada Fitur Dompet Dhuafa - Muhammad Aufa; Madian Muhammad Muchlis (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The development of digital technology has brought significant changes in philanthropy practices, one of which is through the implementation of online fundraising (crowdfunding). This study aims to analyze the effectiveness of implementing fundraising features in the Dompet Dhuafa application as one of the institution's efforts to utilize technological advancements to support philanthropic activities. Using a qualitative approach and literature review, this study examines the factors that influence the success of fundraising through mobile applications, such as trust, ease of use, and perceived usefulness. In addition, other aspects such as interface design, application features, and promotional strategies are also considered in this analysis. The results of the study show that the implementation of fundraising features in the Dompet Dhuafa application has the potential to be an effective means of collecting donations from the wider community, with the caveat that the institution must pay attention to key factors such as transparency, ease of use, and providing clear information about the impact and benefits of donations. The effectiveness of implementing these features can be measured by an increase in the number of donors, the amount of donations collected, and the level of community participation in programs run by Dompet Dhuafa.